ANALISIS PENENTUAN SEKTOR UNGGULAN DENGAN PENDEKATAN PDRB DI KABUPATEN SIMALUNGUN SUMATERA UTARA - Imelda Sari (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the classification of the economic sector (typology) of Simalungun Regency, to determine the sectors that are the basis and non-base sectors in the economy of Simalungun Regency, to determine changes in the Simalungun Regency's economic sector and to determine the leading sectors of Simalungun Regency. This research is located in Simalungun Regency and the research year is 2011-2020. Simalungun Regency is the third largest district in North Sumatra Province and is in a strategic position because it is located in the Lake Toba tourist area, is one of the five Super Priority Tourism Destinations set by President Jokowi in 2019. This type of research is a quantitative descriptive study using three The analysis is Klassen Typology, Location Quotient = LQ and Shift Share. The study findings state that the requirements to become a leading sector are the advanced and fast-growing sector (Klasses typology), the base sector (LQ) and a sector that has high competitiveness (Shift Share) and these three requirements are met by the Agriculture, Forestry, and Fisheries Sector and Government Administration, Defense and Mandatory Social Security Sector. Keywords: Klassen typology, LQ, Shift Share, leading sector, Simalungun Regency